PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Pande Nyoman Juli Andana (2017)
This research was to examine the effect of Firm's Size, Profitability and Institusional ownership variable to Corporate Social Responsibility Disclosure. This research takes sample from 24 companies in mines sector which were listed in Indonesian Stock Exchange, which are publishing financial report and annual report from 2012 - 2015. The method of this research used multiple regression analysis. The result of this study shows that (1) Firm's Size had significant influence to corporate social responsobility Disclosure, (2) Profitability had not significant influence to corporate Social Responsibility Disclosure, (3) Institusional ownership had significant influence ti corporate Social Responsibility Disclosure.